2015
DOI: 10.1097/mnm.0000000000000242
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of tissue alterations in thyroid nodules after microwave ablation

Abstract: B-mode sonography and colour-coded Doppler sonography are easily applicable, providing real-time imaging control for microwave ablation. However, they are limited in accuracy and susceptible to artefacts. Scintigraphic imaging delivers quantifiable, operator-independent results and is promising in the evaluation of treatment success and follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It has been shown that tracer uptake after MWA ablation and during the follow-up was significantly reduced in the ablated tissue. Further research is necessary to establish the real role of scintigraphic imaging in follow-ups after MWA is used in the treatment of benign thyroid nodules [83,84].…”
Section: Clinical Resultsmentioning
confidence: 99%
“…It has been shown that tracer uptake after MWA ablation and during the follow-up was significantly reduced in the ablated tissue. Further research is necessary to establish the real role of scintigraphic imaging in follow-ups after MWA is used in the treatment of benign thyroid nodules [83,84].…”
Section: Clinical Resultsmentioning
confidence: 99%
“…The magnetron in the microwave generator produces microwaves, which can raise the local temperature to 60 to 100 °C and leads to protein denaturation. [ 4 ] In 2000 and 2001, Pacella [ 5 ] and Dupuy [ 6 ] first applied laser ablation and radiofrequency ablation (RFA), respectively, to treat recurrent thyroid carcinoma. Currently, RFA and MWA are mainly used to treat benign thyroid nodules in China.…”
Section: Introductionmentioning
confidence: 99%
“…The MOA technique is a good alternative in the case of MWA or bipolar RFA for TNs ( 20 ). In our experience of treating nodules with a maximum diameter of 2 cm, we only needed four to five overlapping ablations of no more than 2 min for each one to cover >80% of the nodule ( Fig.…”
Section: Discussionmentioning
confidence: 99%